Baseline CD4 cell counts and outcomes among adult treatment naïve HIV patients after taking fixed dose combination GPO-VIR-S and GPO-VIR-Z in Thailand - Nyan Lin Kyaw (2018)
A retrospective study was conducted by reviewing 459 medical records of adult treatment naïve HIV patients who received a fixed dose combination of GPO-VIR-S (stavudine, lamivudine and nevirapine) or GPO-VIR-Z (zidovudine, lamivudine and nevirapine) at Ramathibodi Hospital in Bangkok, Thailand during 2002-2009 following Thai National Treatment Guideline for adults with HIV. The aim of this study was to assess the association between the baseline CD4 cell count and outcome. The median CD4 cell count at baseline, 6, 12 and 102 months were 102 cells/μl, 213 cells/μl, 274 cells/μl and 423 cells/μl. The virologic response (p=0.327), virologic rebound (p=0.626), adverse effects of anti-retroviral therapy (ART) (p=0.976), switching to other ART (p=0.245), occurrence of immune reconstitution inflammatory syndrome (IRIS) (p>0.05) and occurrence of drug resistance (p=0.952) were not significantly associated with baseline CD4 count. The Kaplan-Meier estimate showed the median time (95% CI) to achieve virologic response was 10.4 (9.8-11.0) months and the median time to achieve virologic rebound was 30.0 (21.6-38.4) months after initiation of ART. Analysis showed the median time to achieved virologic response (p=0.401) and virologic rebound (p=0.562) were not significantly associated with the baseline CD4 count. This study shows the outcome after onset of ART did not vary by baseline CD4 cell count.